Respuesta :

Happil

Solving for the Remainder with the Remainder Theorem

Answer:

[tex]3[/tex]

Step-by-step explanation:

According to the Remainder Theorem, if we divide a polynomial, [tex]P(x)[/tex], by [tex]x -\blue a[/tex], the remainder is [tex]P(\blue a)[/tex].

If we let [tex]P(x) = x^2 -1[/tex], the remainder when we divide [tex]P(x)[/tex] by [tex]x -\blue 2[/tex] is [tex]P(\blue 2)[/tex].

The last thing we need to do now is to evaluate [tex]P(\blue 2)[/tex].

[tex]&P(\blue 2) &= &(\blue 2)^2 -1 \\ &P(\blue 2) &= &4 -1 \\ &P(\blue 2) &= &3[/tex]